Two-Step Synthesis of Tungsten and Molybdenum Disulfides; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Irtegov Yu. A. Yuri Aleksandrovich (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen